2007
DOI: 10.1007/s00394-007-0650-2
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle and diet in people using dietary supplements

Abstract: The high prevalence of supplement use in EPIC-Heidelberg was associated with several presumably healthier lifestyle and diet characteristics. This needs to be considered in further evaluations of the risk of chronic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

24
82
2
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(114 citation statements)
references
References 38 publications
24
82
2
6
Order By: Relevance
“…We also found that of 319 participants of the study, most of them [204 (64.4%)] believed that it is important to consume multivitamin products in our day to day lives and 176 (56.1%) participants agreed that multivitamins are essential for good health. The findings in our study corroborates with other afore mentioned studies (Kaur and Sekhri, 2014;Bailey et al, 2011;Gahche et al, 2011;Timbo et al, 2006;Reinert et al, 2007;Qidwai et al, 2012). Side effects were experienced by only a minority and may be due improper utilization of multivitamins.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We also found that of 319 participants of the study, most of them [204 (64.4%)] believed that it is important to consume multivitamin products in our day to day lives and 176 (56.1%) participants agreed that multivitamins are essential for good health. The findings in our study corroborates with other afore mentioned studies (Kaur and Sekhri, 2014;Bailey et al, 2011;Gahche et al, 2011;Timbo et al, 2006;Reinert et al, 2007;Qidwai et al, 2012). Side effects were experienced by only a minority and may be due improper utilization of multivitamins.…”
Section: Discussionsupporting
confidence: 92%
“…In another survey conducted in Columbia to estimate the use of dietary supplements, 73% participants were found to be users of dietary supplements and among them, 85% reported the use of multivitamin supplements (Timbo et al, 2006). Likewise, in a study conducted on 11,929 men in Germany 40% population reported use of vitamin or mineral supplements (Reinert et al, 2007). Though all the previously mentioned studies report high multivitamin use, in our study less than half the participants (46.5%) consumed multivitamin products.…”
Section: Discussioncontrasting
confidence: 43%
“…Other surveys carried out in Europe (4)(5)(6)(7)(8)(9)(10)(11)(12)(13) have used different tools to assess food supplement use, such as mailed questionnaires and telephone or face-to-face interviews. Some studies focused specifically on the use of food supplements while others were wider-ranging surveys that also included questions regarding the use of food supplements, often within FFQ or food diaries or other methodologies.…”
Section: Discussionmentioning
confidence: 99%
“…Various surveys on the use of food supplements and/or functional foods have been carried out in European countries, in which information about the demographic, physical, lifestyle and health characteristics of food supplement users have also been collected (4)(5)(6)(7)(8)(9)(10)(11)(12)(13) . In most cases the variables found to be related to supplement use were age, gender, education, income and lifestyle variables such as drinking, smoking and exercising (4)(5)(6)(7)(8)(9)(10) . Significant differences in food consumption were also observed, indicating a tendency for healthier food choices among users of supplements (4,6,11) .…”
mentioning
confidence: 99%
See 1 more Smart Citation